2014
DOI: 10.1063/1.4864132
|View full text |Cite
|
Sign up to set email alerts
|

Controllable nonlinear refraction characteristics in hydrogenated nanocrystalline silicon

Abstract: Nonlinear refraction (NLR) of hydrogenated nanocrystalline silicon (nc-Si:H) has been investigated through the close aperture Z-scan method. We demonstrate a significant NLR and a unique feature of controllable NLR characteristics between saturable and Kerr NLR with the incident photon energy. We numerically evaluate the proportion of these two mechanisms in different wavelengths by a modified NLR equation. The band tail of nc-Si:H appears to play a crucial role in such NLR responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…The third operator, = exp { i k 0 n 0 / 2 z z + normalΔ z false[ n 2 ( x , y , z , t ) / n 0 2 1 false] d z } incorporates the NL phase-shift induced by NLR through n = n 0 + n normalN normalL = ( 0 + η 0 N 0 ) + ( η 1 N 1 + η 2 N 2 ) , where η j is the refraction volume of the j -the electronic energy level . The last two operators, P̂ and  conclude the beam propagation in a step Δ z , where the resulting field will be used as an initial condition for the next step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third operator, = exp { i k 0 n 0 / 2 z z + normalΔ z false[ n 2 ( x , y , z , t ) / n 0 2 1 false] d z } incorporates the NL phase-shift induced by NLR through n = n 0 + n normalN normalL = ( 0 + η 0 N 0 ) + ( η 1 N 1 + η 2 N 2 ) , where η j is the refraction volume of the j -the electronic energy level . The last two operators, P̂ and  conclude the beam propagation in a step Δ z , where the resulting field will be used as an initial condition for the next step.…”
Section: Resultsmentioning
confidence: 99%
“…relates to the propagation through distance Δz/2, in a homogeneous medium with linear refractive index n 0 and transverse derivative ∇ = + = + + + where η j is the refraction volume of the j-the electronic energy level. 45 The last two operators, P ̂and A ̂conclude the beam propagation in a step Δz, where the resulting field will be used as an initial condition for the next step. After sequentially performing N iterations, the Fresnel−Kirchhoff diffraction formula within the Fresnel approximation was used to model the external propagation in the far-field, following the method described by Hughes et al 44 The results of the BPM simulation, in the OA and CA Z-scan schemes, for samples with different MIC concentrations and input peak intensities, are represented by solid lines in Figures 4 and 6.…”
Section: Nl Opticalmentioning
confidence: 99%
“…Thus, research advances in this field depend critically and primarily on the development of new materials with strong NLO capabilities and effective tailoring of their NLO properties. During the past years, many peculiar NLO materials, such as Au and Pt nanoparticles, [8][9][10] nanocrystalline Si and Si/SiO 2 multilayers, [11][12][13] graphene and graphene-doped polymer, 14,15 PMMA films, 16 and pyrrole methine, 17 have been widely investigated and demonstrated that their application field can be enormously extended by tailoring their NLO properties.…”
mentioning
confidence: 99%
“…Such a E g variation is large enough to permit the transformation process happening because the NLO absorption switching is critically sensitive to the energy variation even it is less than tens meV. 11,12 The mechanism for the influence of the E g on the switching is discussed as follows. In our previous work, the intermediate energy levels (i.e., defect states) have been demonstrated in BNT thin films.…”
mentioning
confidence: 99%
See 1 more Smart Citation